Pelatihan Akuntansi Bagi Pengelola BUMDes di Desa Taba Terunjam Kec. Karang Tinggi Keb . Bengkulu Tengah - Hanila, Siti; Pardi, Sri Handayani; Prawitasari, Andriyani; Fitriano, Yun; Pratama, Meylan (Universitas Dehasen Bengkulu, 2022)
As an economic driver, BUMDes managers are expected to fulfill their obligations, including preparing financial reports. Based on this financial report, the financial performance, volume of BUMDes business, and the amount to be distributed to financiers will be determined as profit sharing to the village government or village business results. BUMDes have been established in various villages. BUMDes businesses that have been established include: salon services, table and chair rental, savings and loan services and convenience stores. In the process of preparing these financial statements, BUMDes also needs to determine the accounting policies adopted. The accounting policy to be selected is available in the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) published by the Indonesian Institute of Accountants (2016). BUMDes managers have attempted to report their responsibilities through financial reports. The importance of BUMDes managers is obliged to develop an adequate accounting system. An adequate accounting system in preparing financial reports includes, among others, the preparation of account codes, account names, general journal books, cash books, bank books, accounts receivable books, goods books, and trial balances. Our service team organizes technical skills training for BUMDes managers in compiling financial reports in accordance with SAK-EMKM. Community Service Activities (PKM) are carried out for 1 month located in Taba Terunjam Village, District, Karang Tinggi Regency, Central Bengkulu This training method is a lecture accompanied by hands-on practice for participants to prepare financial reports with an accounting system in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) published by the Indonesian Institute of Accountants. The basic things that must be understood by participants include the definition of